PROPER NAMES AS A CONSTITUENT OF BIOGRAPHICAL NARRATIVE AND THEIR TRANSLATION - Бялик, Василь Дмитрович; Добровольська, Анастасія (Науковий вісник Чернівецького національного університету імені Юрія Федьковича, 2024)
The article examines the peculiarities of translating proper names in a biographical novel, in particular, on the example of Michelle Obama's book Becoming and its Ukrainian translation by M. Hotsatsiuk. The book Becoming is a memoir by Michelle Obama, the former First Lady of the United States, which was published on 13 November 2018. Proper names, such as names, place names, and institutions, play a significant role in creating an authentic cultural and historical context for the work. Thanks to such elements, readers can better understand the lives, events and motivations of the characters, feeling a closer connection with the text. The article analyses approaches to the translation of proper names, including transcription, transliteration, calque, and mixed transcoding, in particular, on the example of such onyms as ‘White House’, ‘South Side’, and the names of Michelle Obama and her family members. The author explores how these methods affect the perception of the text by readers of a different language and cultural system. The results of the study emphasise the importance of the cultural context and lexical transformations necessary to preserve the original idea and mood of the work, which is especially important in biographical literature. In addition, the article demonstrates how the successful reproduction of proper names in translation helps to restore the multidimensionality of the text, reflecting not only the literal meaning but also the atmosphere and cultural features of the original. Thus, the article makes a contribution to the field of translation studies by emphasising the importance of taking linguistic and cultural aspects into account when translating biographical works, which contributes to the adequate perception of the text in the translated version and preserving its authenticity.
Keywords: cultural context, identifier, identity, memoirs, narrative, onyme, proper names, translation